International coach developer framework (ICCE Global Coching Office, 2024)
Written by a team of expert Coach Developers (practitioners and academics) from around the world, ICDF 2nd edition is for anyone involved in the development of coaches, from the club coach helping other coaches to those responsible for the quality and management of their coaching and Coach Developer workforce in their organisation. It has been written for clubs, individual sports organisations and multi-sport coaching organisations wishing to improve their coaches, as well as institutes of higher education that deliver coaching courses and programmes. It will also benefit individual Coach Developers intent upon improving the way they work with coaches. It draws on the growing research in the field and includes examples of good practice from across the world, demonstrating the importance of creating systems and programmes appropriate to the culture, context and specific needs of each organisation.